2011
DOI: 10.1002/jobm.201100095
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and diversity of phosphate mineralizing bacteria in the coral reefs of Gulf of Mannar

Abstract: Phosphatase Producing Bacteria (PPB) and Inorganic Phosphate Solubilizing Bacteria (IPSB) are important to reef nutrition. These microbes and phosphate concentration play a significant role in the productivity of coral reef ecosystems. A study was conducted in Gulf of Mannar coral reef ecosystem to understand the diversity of these groups of bacteria and their competence in mineralizing the phosphate. The PPB isolates were identified under six genera i.e. Bacillus, Pseudomonas, Micrococcus, Vibrio, Arthrobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…Recent studies in the mid-west coastal estuaries of India also show Bacillus as dominant with high abilities to efficiently degrade carbohydrates [37]. Their role as an important fraction of the phosphate mineralizing bacteria in the coral-reefs of the Gulf-of Mannar, in southern peninsular India, has been documented quite recently [33]. As the neighbor joining boot-strap consensus tree brings out their phylogenetic heterogeneity (Fig.…”
Section: Taxonomic Diversity Of Bacteriamentioning
confidence: 85%
“…Recent studies in the mid-west coastal estuaries of India also show Bacillus as dominant with high abilities to efficiently degrade carbohydrates [37]. Their role as an important fraction of the phosphate mineralizing bacteria in the coral-reefs of the Gulf-of Mannar, in southern peninsular India, has been documented quite recently [33]. As the neighbor joining boot-strap consensus tree brings out their phylogenetic heterogeneity (Fig.…”
Section: Taxonomic Diversity Of Bacteriamentioning
confidence: 85%
“…B. megaterium strain 573 isolated from coral Fig. 3 Effect of bacterial inoculation on root elongation of tomato seedlings reefs of Gulf of Mannar showed very high (0.906 mmol/L P) mineral phosphate solubilization (Kannapiran and Ravindran 2012). Chen et al (2006) reported P solubilization by B. megaterium (CC-BC10) to the tune of 270.2 mg/L.…”
Section: Discussionmentioning
confidence: 99%
“…starch, casein, tween 80, toluidine blue and urea, respectively 27 . Alkaline phosphatase 38 and Nitrate reductase 39 were also checked for these cultures. After spot inoculation, the plates were incubated for 4 days at 25 ± 1 °C.…”
Section: Methodsmentioning
confidence: 99%